A multi-tissue human knee single-cell atlas identifies that osteoarthritis reduces regenerative tissue stem cells while increasing inflammatory pain macrophages - Rajnikant Dilip Raut; Amit Kumar Chakraborty; Tuhina Neogi; Michael Albro; Brian Snyder; Thomas P. Schaer; Chao Zhang; Mark W. Grinstaff; Manish V. Bais (Communications Biology)
Abstract Osteoarthritis (OA) affects the entire knee joint, yet cross-tissue molecular interplay remains poorly understood. To address this, we constructed the first single-cell RNA sequencing atlas of knee OA, profiling articular cartilage, meniscus, synovium, and subchondral bone. Our analysis revealed that healthy synovium and meniscus harbor abundant tissue stem cells (TSCs) and immune cells, which are significantly altered in OA. Regenerative TSCs expressing SDF1, SOX9, CD146, PDGFRB, and CD105 are reduced, while osteogenic TSCs marked by NT5E are expanded. OA cartilage has distinct MMP13-producing detrimental chondrocytes while increasing RUNX2-producing chondrocytes and fibroblasts. OA tissues are enriched with inflammatory (IL1B-IL6-NOS2-TNF) and pain-marker (P2RX7)-specific macrophages, inflammatory genes expression and immune cells. Cell-cell communication contributes to OA progression, promotes proinflammatory macrophages, and osteogenic TSCs. By identifying these OA-specific cells and molecular interplay, and constructing the first multi-tissue comprehensive atlas, we bridge the critical knowledge gaps and lay the foundation for advancing targeted OA therapies.